Inflammatory biomarkers of frailty: A review - Zhang, Liying; Zeng, Xiaofeng; He, Fuqian; Huang, Xiaoli (Experimental gerontology, 2023)
Frailty is a common geriatric syndrome characterized by increased vulnerability and is associated with adverse clinical events such as falls, hospitalization, and death. Early diagnosis and early intervention can delay or reverse frailty and ensure the healthy aging of older individuals. At present, there are no gold standard biomarkers for the diagnosis of frailty, which mainly relies on the scale to assess frailty, and the scale has shortcomings such as lagging assessment, subjectivity, and poor consistency. Frailty biomarkers help in early diagnosis and intervention in frailty. The purpose of this review is to summarize the existing inflammatory markers of frailty and focus on novel inflammatory biomarkers of frailty that can be used to help identify frailty early and explore potential intervention targets. •Inflammation is closely related to frailty, and the study of frailty and inflammation is in full swing.•The latest research findings, including inflammaging, and potential biomarkers of frailty were summarized.•Exploring the specific biomarkers of frailty is helpful to assess frailty and ensure the healthy aging of older adults.